Application of Genetic Algorithms in Vehicle Routing Problems - Hasnah Moin, Noor (Malaysian Journal of Science, 2002)
In this paper we propose four methods based on Genetic Algorithms for Vehicle Routing Problems. It is observed that algorithms that construct the routes sequentially produce superior results compared to parallel route building methods. In general, savings GA performs well for all the problems tested whilst vertex sequencing method produces superior solutions for small problems.